2020
DOI: 10.1017/s0047279420000021
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Universal Credit Rollout on Housing Security: An Analysis of Landlord Repossession Rates in English Local Authorities

Abstract: Housing allowances within the UK’s welfare system help protect low-income households from eviction. Universal Credit (UC) has faced criticism for threatening this with its long wait periods, increased conditionality and monthly direct payments. However, there is currently a lack of robust, national-level quantitative analysis on UC’s housing security impacts. This article addresses this, exploiting cross-area variation in the timing of UC rollout to assess its impact on landlord repossession rates within 323 E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
(3 reference statements)
1
19
0
Order By: Relevance
“…UC The regressive distributional impact of UC may have been amplified by the delays in benefit payments. 19 To mimic a typical salary, UC payments are made in arrears once a month directly into the claimants' bank account. Given that payments take one week to reach the bank account of the recipient, the first payment should be received around six weeks after the original application.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UC The regressive distributional impact of UC may have been amplified by the delays in benefit payments. 19 To mimic a typical salary, UC payments are made in arrears once a month directly into the claimants' bank account. Given that payments take one week to reach the bank account of the recipient, the first payment should be received around six weeks after the original application.…”
Section: Discussionmentioning
confidence: 99%
“…20 The higher volume of sanctions has decreased the amount of benefits received by subgroup of individuals that failed to meet the requirements imposed by the Claimant Commitment. 21 We note the larger majority of recipients being sanctioned are male and in the 16-24 age 19 Late payments can arise because the verification process is not completed on-time (either by DWP or the claimant), claims are amended at a late stage, or any other sort of technical difficulty. 20 Prior to the Welfare Reform Act 2012, the maximum period for which a claimant's benefit could be stopped for a breach of the rules was six months.…”
Section: Discussionmentioning
confidence: 99%
“…The regressive distributional impact of UC may have been amplified by the delays in benefit payments. 19 To mimic a typical salary, UC payments are made in arrears once a month directly into the claimants' bank account. Given that payments take one week to reach the bank account of the recipient, the first payment should be received around six weeks after the original application.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of Universal Credit has been widely criticized and it has generated enormous controversy. Mounting evidence in sociology, political science, and medical literature suggests Universal Credit has led to increased food bank usage, consultations in general practices, landlord repossession rates, and created mental health difficulties amongst claimants (Arie, 2018;Loopstra et al, 2018;Cheetham et al, 2019;Hardie, 2020;Wickham et al, 2020). This paper contributes to the Economics literature by providing the first empirical evaluation of the criminogenic effects of Universal Credit based on quasi-experimental methods and high-frequency data.…”
Section: Introductionmentioning
confidence: 96%
“…One area concerns the housing impacts of benefit sanctions, in terms of rent arrears, eviction and homelessness. A recent UK study by Hardie (2020), examining the effects of the recently implemented Universal Credit programme (which merges pre-existing meanstested working-age benefits), found that benefit conditionality and sanctioning were associated with increased landlord repossession rates. An additional area where we found either inconsistent or limited evidence concerns child well-being, including educational and health outcomes.…”
Section: Literature Gapsmentioning
confidence: 99%